Motor and somatosensory degenerative myelopathy responsive to pantothenic acid in piglets. Issue 1 (January 2023) - Lorenzett, Marina P.; Armién, Aníbal G.; Henker, Luan C.; Schwertz, Claiton I.; Cruz, Raquel A. S.; Panziera, Welden; de Barros, Claudio S. L.; Driemeier, David; Pavarini, Saulo P.
This report describes 2 events of degenerative myelopathy in 4- to 27-day-old piglets, with mortality rates reaching 40%. Sows were fed rations containing low levels of pantothenic acid. Piglets presented with severe depression, weakness, ataxia, and paresis, which were more pronounced in the pelvic limbs. No significant gross lesions were observed. Histologically, there were degeneration and necrosis of neurons in the spinal cord, primarily in the thoracic nucleus in the thoracic and lumbar segments, and motor neurons in nucleus IX of the ventral horn in the cervical and lumbar intumescence. Minimal-to-moderate axonal and myelin degeneration was observed in the dorsal funiculus of the spinal cord and in the dorsal and ventral nerve roots. Immunohistochemistry demonstrated depletion of acetylcholine neurotransmitters in motor neurons and accumulation of neurofilaments in the perikaryon of neurons in the thoracic nucleus and motor neurons. Ultrastructurally, the thoracic nucleus neurons and motor neurons showed dissolution of Nissl granulation. The topographical distribution of the lesions indicates damage to the second-order neurons of the spinocerebellar tract, first-order axon cuneocerebellar tract, and dorsal column-medial lemniscus pathway as the cause of the conscious and unconscious proprioceptive deficit, and damage to the alpha motor neuron as the cause of the motor deficit. Clinical signs reversed and no new cases occurred after pantothenic acid levels were corrected in the ration, and piglets received parenteral administration of pantothenic acid. This study highlights the important and practical use of detailed neuropathological analysis to refine differential diagnosis.